Determinan Era Keuangan Digital, Jejaring Sosial, Peningkatan Penjualan terhadap Pertumbuhan Usaha Wirausaha Muda di Tangerang (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the impact of digital finance and social networks on sales and business growth among young entrepreneurs in Tangerang. It examines how digital financial services help access capital, improve transaction efficiency, and expand markets, as well as the role of social networks as a marketing medium to enhance sales and customer loyalty. Using a quantitative approach, data were collected through an online questionnaire from young entrepreneurs actively using digital finance and social networks, supported by in-depth interviews for qualitative insights. Regression analysis tested the relationship between digital finance, social networks, sales growth, and business growth. The R-Square value of 0.221 indicates that the independent variables explain only 22.1% of the variation in business growth, while the remaining 77.9% is influenced by other factors such as capital, innovation, government support, managerial competence, and the business environment. Results show that digital finance has a negative and significant effect on young entrepreneurs’ growth (coefficient = -0.204, p = 0.028), while social networking has a positive but marginally significant effect (coefficient = 0.227, p = 0.050). Sales increase shows the strongest positive and significant impact on business growth (coefficient = 0.400, p = 0.001). These findings highlight that while digital finance and social networks contribute to growth, sales performance remains the key driver for young entrepreneurs.